PERGESERAN SIKAP INDIA TERHADAP MYANMAR DARI KONFRONTATIF MENUJU KOOPERATIF (1991-2011) - , SUGIARTO PRAMONO; , Prof. Dr. Jahja Muhaimin, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Shift in the attitude of India towards Myanmar from confrontational to cooperative which occurred between 1991 until 2011 is driven by a series of factors at both the domestic and international. At the domestic level, collaboration between the business interests with the rulers were behind Indiaâs approach to Myanmar while at the international level, a number of events push India to choose that way. The collapse of the Soviet Union